The coexistence of arbuscular mycorrhizal fungi and dark septate endophytes synergistically enhanced the cadmium tolerance of maize - Wang, Zhaodi; Wang, Lei; Liang, Xinran; Zhang, Guangqun; Li, Zuran; Yang, Zhixin; Zhan, Fangdong (Frontiers in Plant Science, 2024)
Introduction Arbuscular mycorrhizal fungi (AMF) and dark septate endophytic fungi (DSEs) generally coexist in the roots of plants. However, our understanding of the effects of their coexistence on plant growth and stress resistance is limited. Methods In the present study, the effects of single and dual inoculation of AMF and DSE on the growth, photosynthetic physiology, glutathione (GSH) metabolism, endogenous hormones, and cadmium (Cd) content of maize under 25 mg•kg-1 Cd stress were investigated. Results Compared with that after the non-inoculation treatment, AMF+DSE co-inoculation significantly increased the photosynthetic rate (Pn) of maize leaves; promoted root GSH metabolism; increased the root GSH concentration and activity of γ-glutamyl cysteine synthase (γ-GCS), ATP sulfatase (ATPS) and sulfite reductase (SIR) by 215%, 117%, 50%, and 36%, respectively; and increased the concentration of endogenous hormones in roots, with increases in zeatin (ZR), indole-3 acetic acid (IAA), and abscisic acid (ABA) by 81%, 209%, and 72%, respectively. AMF inoculation, DSE inoculation and AMF+DSE co-inoculation significantly increased maize biomass, and single inoculation with AMF or DSE increased the Cd concentration in roots by 104% or 120%, respectively. Moreover, significant or highly significant positive correlations were observed between the contents of ZR, IAA, and ABA and the activities of γ-GCS, ATPS, and SIR and the glutathione (GSH) content. There were significant or highly significant positive interactions between AMF and DSE on the Pn of leaves, root GSH metabolism, and endogenous hormone contents according to two-way analysis of variance. Therefore, the coexistence of AMF and DSE synergistically enhanced the Cd tolerance of maize.